1997
DOI: 10.1002/(sici)1096-9861(19970804)384:3<443::aid-cne9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic axonal contacts on identified cat trigeminal motoneurons and their correlation with medullary raphe nucleus stimulation

Abstract: The innervation of the trigeminal motor nucleus by serotonergic fibers with cell bodies in the raphe nuclei pallidus and obscurus suggests that activation of this pathway may alter the excitability of trigeminal motoneurons. Thus, we recorded intracellular responses from cat jaw-closing (JC) andjaw-opening (JO) alpha-motoneurons evoked by raphe stimulation and used a combination of intracellular staining of horseradish peroxidase (HRP) and immunohistochemistry at the light and electron microscopic levels to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 78 publications
(90 reference statements)
0
24
0
1
Order By: Relevance
“…Results obtained by Takatori et al (57) suggested that NRP and NRO exerted mainly a direct inhibitory influence on masseter motoneurons. Nagase et al (18) observed just a facilitatory influence of non-serotonergic (and serotonergic) neurons in NRP and NRO directly afferenting jaw-opener (mylohyoid) and jaw-closer (masseter) motoneurons. The cross-correlation involving the digastric muscle here was negative and that involving the masseter muscle was positive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results obtained by Takatori et al (57) suggested that NRP and NRO exerted mainly a direct inhibitory influence on masseter motoneurons. Nagase et al (18) observed just a facilitatory influence of non-serotonergic (and serotonergic) neurons in NRP and NRO directly afferenting jaw-opener (mylohyoid) and jaw-closer (masseter) motoneurons. The cross-correlation involving the digastric muscle here was negative and that involving the masseter muscle was positive.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known target structures are the trigeminal motor nucleus (1), facial nucleus (2), nucleus ambiguus (3), hypoglossus nucleus (4,5), the ventral horn of the spinal cord (6)(7)(8), the medial medul-lary reticular formation (9), the ventral respiratory group (10), the red nucleus (11), the dorsal motor nucleus of the vagus (12), the intermediolateral cell column of the spinal cord (13)(14)(15) and the rostral ventrolateral medulla and surrounding regions (9,16,17). At least part of the axons terminate directly in motoneurons (7,18) or preganglionic autonomic neurons (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, a região perifornicial da LH ainda possui eferências para o CeA (Touzani et al, 1996), e o CeA também se projeta para a LH (LeDoux et al, 1988) (Guridi et al, 82 1996) e humanos (Kumar et al, 1998) ) e gera um aumento do tônus do masseter (Sunden-Kuronen et al, 1983). A serotonina age na região perifornicial da LH (Kumar et al, 2007), além de atuar no Me5 e diretamente no Mo5 (Nagase et al, 1997).…”
Section: Considerações Clínicasunclassified